2015
DOI: 10.1007/s10008-015-3010-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal shock resistant composite cathode material Sm0.5Sr0.5CoO3–δ–La0.6Sr0.4FeO3–δ for solid oxide fuel cells

Abstract: The Sm 0.5 Sr 0.5 CoO 3-δ -La 0.6 Sr 0.4 FeO 3-δ 1:1 composite, obtained by sintering mixture of components, was tested as a prospective cathode material for the oxygen reduction reaction in solid oxide fuel cells. Catalytic activity of the prepared material was characterized using electrochemical impedance spectroscopy at 400, 450, 500, 550, 600, 650, and 700°C in oxygen and oxygen-argon mixtures in half-cells with Sm 0.2 Ce 0.8 O 1.9 as the electrolyte. Relatively low activation energies (65.2, 66.9, and 56.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For example, the peak power densities at 750 • C were 712 and 993 mW/cm 2 for the bare and for the modified LSF-GDC, respectively, enhanced by 39.5% via the impregnation of BaCO 3 nanoparticles. This enhancement was significantly higher compared to the previous report on anode-supported cells based on LSF/LSF-GDC cathodes[22,25,33]. Figure7ddisplays the stability of NiO-YSZ-anode-supported SOFC with modified LSF-GDC cathode under a fixed voltage of 0.7 V. It was found that the measured current density of the single-cell was kept stable at ~700 mA/cm 2 , indicating excellent performance stability for about 100 h at 700 • C.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…For example, the peak power densities at 750 • C were 712 and 993 mW/cm 2 for the bare and for the modified LSF-GDC, respectively, enhanced by 39.5% via the impregnation of BaCO 3 nanoparticles. This enhancement was significantly higher compared to the previous report on anode-supported cells based on LSF/LSF-GDC cathodes[22,25,33]. Figure7ddisplays the stability of NiO-YSZ-anode-supported SOFC with modified LSF-GDC cathode under a fixed voltage of 0.7 V. It was found that the measured current density of the single-cell was kept stable at ~700 mA/cm 2 , indicating excellent performance stability for about 100 h at 700 • C.…”
mentioning
confidence: 72%
“…However, its performance is still inadequate compared to the requirements of cathode materials for IT-SOFCs. Consequently, several approaches have been proposed, to enhance the performance of LSF electrode materials for IT-SOFCs, such as developing composite cathodes, doping other metal ions, and surface modification [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…54 For example, to provide thermal compatibility between electrodes and electrolytes, composites such as cathodes made with Sm 0.5 Sr 0.5 CoO 3−δ (SSC) and ceria-based electrolytes have shown better thermal resistance than Sm 0.5 Sr 0.5 CoO 3−δ (SSC) to match compatibility with ceria electrolytes. 55 In addition, in ammonia-fueled solid oxide fuel cells, with state-of-the-art nickel-based electrodes, nitridation of the electrodes during thermal cycling occurs, which could result in severe performance degradation due to irreversible morphological changes in the anode microstructure and respective electrochemical properties. 36,56 The extent of nitrification depends upon the ammonia cracking reaction rate.…”
Section: Thermal Shocksmentioning
confidence: 99%